Retroperitoneal hydatid cyst at a rare site- a case report - Dr. Shramika Naik; Dr. Janice Jaison; Dr. Smita Bhide; Dr. Sneha R. Joshi (Tropical Journal of Pathology and Microbiology, 2019)
Hydatid disease in humans is caused by the parasite Echinococcus Granulosus. It is most commonly found in liver and lungs. Primary Retroperitoneal Hydatid cyst is extremely rare and constitutes only 0.8% of total cases. We present a case of a 42 year old female who presented with a historyof gradually increasing abdominal mass. A clinical diagnosis of Pancreatic cystic neoplasm was made and Whipple's procedure was performed. A histopathological diagnosis of Retroperitoneal Hydatid cyst was given. The diagnosis of hydatid disease should be considered in the differential diagnosis of all cystic lesions at all anatomic locations, particularly in areas where the condition is endemic.